Comparação de efeitos dos extratos de Hypericum perforatum (Hipérico) e de Mentha crispa (Hortelã) em diferentes modelos experiemtais - Santos Filho, Sebastião David dos (2007)
Several clinic evaluations have been possible with radiobiocomplexes labeled with technetium-99m (99mTc). Some natural and synthetic drugs are capable of to interfere on the labeling of blood constituents with 99mTc, as well as on the biodistribution of radiobiocomplexes. Authors have also reported about the toxicity of several natural products. The aim of this study was to compare the effects of the Mentha crispa (hortelã) and of the Hypericum perforatum (hipérico) in different experimental models. On the labeling of red blood cells (RBC) and plasma and cellular proteins with 99mTc, both extracts were capable of to decrease the radioactivity percentage on the cellular compartment and on the fixation on plasma and cellular proteins. On the morphometry of the RBC, only the hortelã was capable to alter the shape and the perimeter/area ratio of the RBC. On the biodistribution of the radiobiocomplex sodium pertechnetate (Na99mTcO4), the hortelã increased the Na99mTcO4 distribution in the kidney, spleen, liver and thyroid, meanwhile the hipérico decreased the Na99mTcO4 distribution in the bone, stomach, lungs and thyroid, and increased the Na99mTcO4 distribution in the pancreas. On the bacterial cultures survival, the hipérico was capable of to protect the bacteria against the stannous chloride (SnCl2) effect. The hipérico did not alter the topology of plasmidial DNA and did not protect the plasmidial DNA against the SnCl2 action. Probably, the effects presented by both extracts could be due to chemical compounds of the extracts that could alter the morphology of the RBC and the plasma membrane ions transport, and/or by phytocomplexes that could be formed with different effects dependent on the biological system considered